Late cortical plasticity in motor and auditory cortex: role of met-allele in BDNF Val66Met polymorphism. (9th January 2014) - Teo, James T. H.; Bentley, Graham; Lawrence, Philip; Soltesz, Fruzsina; Miller, Sam; Willé, David; McHugh, Simon; Dodds, Chris; Lu, Bai; Croft, Rodney J.; Bullmore, Edward T.; Nathan, Pradeep J.
Abstract: The brain-derived neurotropic factor (BDNF) Val66Met polymorphism has been associated with abnormalities of synaptic plasticity in animal models, and abnormalities in motor cortical plasticity have also been described in humans using transcranial direct current stimulation. No study has yet been done on plasticity in non-motor regions, and the effect of two Met alleles (i.e. 'Met dose') is not well understood. We studied the effect of the BDNF Val66Met polymorphism on the after-effects of transcranial direct current stimulation and tetanic auditory stimulation in 65 subjects (23; Val66Val, 22; Val66Met and 20; Met66Met genotypes). In the first session, motor evoked potentials (MEP) were recorded under stereotaxic guidance for 90 min after 9 min of anodal transcranial direct current stimulation (TDCS). In the second session, auditory-evoked potentials (AEP) were recorded before and after 2 min of auditory 13 Hz tetanic stimulation. There was a difference in MEP facilitation post-TDCS comparing Met carriers with non-Met carriers, with Met carriers having a modest late facilitation at 30–90 min. There was no difference in responses between Val66Met genotype and Met66Met genotype subjects. Tetanic auditory stimulation also produced late facilitation of N1-P2 AEP at 25 min, but there was no apparent effect of genetic status. This study indicates that Met66Met carriers behave like Val66Met carriers for TDCS-induced plasticity, and produce a late facilitation of MEPs. Auditory cortical plasticity was not affected by the BDNF Val66Met polymorphism. This study sheds light on the differences between auditory and motor cortical plasticity and the role of the BDNF Val66Met polymorphism.